DEVELOPING ENGLISH READING MATERIALS OF NARRATIVE TEXT BASED ON PROJECT BASED LEARNING FOR NINTH GRADE AT SMP NEGERI 8 MEDAN - Tri Purnama Nasution; Rika Julia (Universitas Negeri Medan, 2023)
The objective of this study was to develop materials for reading of narrative text. This study was carried out at SMP Negeri 8 Medan. This research was based on Research and Development (R&D). It contained six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising materials, and final product. The data were gathered through the distribution of questionnaire for pupils and interviewed an English teacher to get the pupils’ need. The product has been validated by two experts in percentage. The average score of experts’ validations was 94.2% in content aspect, the presentation aspect was 95%, the language aspect was 96.6%, and the layout was 95%. The average score was 95.2% which categorized as very good. This study concluded that the developed materials of narrative text which based on Project Based Learning may be used as teaching materials of narrative text at Junior High School level. Keyword: Materials, Reading, Narrative Text, Research and Development, Project Based Learning